Slave Revolts in Antiquity. (Acumen, 2008)
Although much has been written on Greek and Roman slavery, slave resistance has typically been dismissed as historically insignificant and those revolts that are documented are portrayed as wholly exceptional and resulting from peculiar historical circumstances that had little to do with the intrinsic views or organizational capabilities of the slaves themselves. In this book Theresa Urbainczyk challenges the current orthodoxy and argues that there were many more slave revolts than is usually assumed and they were far from insignificant historically.